2021
DOI: 10.1002/ccd.29705
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with the fourth generation MitraClip™ : Outcomes, procedural aspects, and considerations for device selection

Abstract: Objectives We present our initial experience with the fourth‐generation MitraClip™ (G4) system and propose preliminary criteria for device selection. Background The MitraClip™ G4 system recently underwent a “controlled release” for transcatheter edge‐to‐edge mitral valve repair. The four new devices include technical improvements such as controlled gripper actuation (independent leaflet capture) and continuous left atrial pressure monitoring. To date, a patient‐specific device selection algorithm, and the tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…High safety and efficacy of the G4 system, with 96.5% of patients having reduction in MR grade to 2+ at 30 days were reported. Garcia-Sayan et al [38] also reported similar outcomes in their cohort of 61 patients. They reported procedural success rate of 96.7% and technical failure rate of 1.6%.…”
Section: Food and Drug Admins (Fda) Approved Devicessupporting
confidence: 53%
“…High safety and efficacy of the G4 system, with 96.5% of patients having reduction in MR grade to 2+ at 30 days were reported. Garcia-Sayan et al [38] also reported similar outcomes in their cohort of 61 patients. They reported procedural success rate of 96.7% and technical failure rate of 1.6%.…”
Section: Food and Drug Admins (Fda) Approved Devicessupporting
confidence: 53%
“…Similar with other TEER devices, the ValveClasp systems also need to be tested before they were introduced in vascular approach, but the process has been simplified (only six steps) 1 : Testing the bending properties of the outer deflectable guiding sheath (from 0° to 90°); 2 Testing the bending properties of the inner deflectable guiding sheath (from 0° to 135°); 3 Pushing forward, pulling back, and rotating the clip control system to test the smoothness between the clip control system and the inner sheath when the control system passes through the inner sheath; 4 Opening the clip arms (from 0° to 270°) by twisting the control system knob, then closing the clip arms by rotating the knob in the opposite direction. Next, lock the clip and rotate the knob to see if the clip arms are open 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the current improvement appears to be below the anticipated level; the maximum width of The G4 clip device is only 6 mm, which might not be sufficient. As a result, between 30% and 50% of patients still require more than one clip to be deployed during an operation, which adds to the complexity of the process, lengthens its duration, and increases the risk of complications 3,4 . Wider clips are expected according to the MitraClip G4 procedure outcomes; however, the G4 clamp arm is rigid and challenging to expand further.…”
Section: Disscusionsmentioning
confidence: 99%
See 2 more Smart Citations